Click, release, and fluoresce: In-vivo generation of CO with concomitant synthesis of a fluorescent reporter. (15th August 2021) - De La Cruz, Ladie Kimberly; Ji, Xingyue; Yang, Xiaoxiao; Wang, Binghe
Graphical abstract: Abstract: Delivering a therapeutically active gaseous molecule represents very unique challenges in terms of both precise dosing and concentration assessment. To overcome these obstacles, there have been recent reports of using prodrug approaches for the in-vitro and in-vivo generation of carbon monoxide (CO), which is an endogenous signaling molecule with validated therapeutic efficacy in a range of animal models. Some key components of these approaches include the use of a hydrophobicity-driven Diels-Alder reaction under physiological conditions followed by a cheletropic reaction of the corresponding norbornadien-7-one intermediate, leading to extrusion of CO. With proper design, the same approach also leads to the formation of a fluorescent reporter, allowing for quantitative assessment of the amount of CO released. All these allow for a strategy of "click, release, and fluoresce" in delivering a precise dose of carbon monoxide with the ability to "self-report" delivery quantity and efficiency. This strategy has also been further refined to construct a CO delivery platform with additional functionalities such as bioorthogonal labeling, targeting, triggered release, and simultaneously delivery of more than one payload. This review highlights recent developments in this area.